Determination of Urinary Gluten Immunogenic Peptides to Assess Adherence to the Gluten-Free Diet: A Randomized, Double-Blind, Controlled Study. Issue 10 (6th October 2021) - Monachesi, Chiara; Verma, Anil K.; Catassi, Giulia N.; Franceschini, Elisa; Gatti, Simona; Gesuita, Rosaria; Lionetti, Elena; Catassi, Carlo
Abstract : INTRODUCTION: The adherence to a gluten-free diet (GFD) is a trending topic in the management of celiac disease. The aim of our study was to evaluate the diagnostic performance of urinary gluten immunogenic peptides (GIP) determination to detect gluten contamination of the GFD. METHODS: In study A, 25 healthy adults on a standard GFD performed 6 gluten challenges (0, 10, 50, 100, 500, and 1, 000 mg) with quantification of urinary GIP before (T0 ) and during the following 24 hours. In study B, 12 participants on a gluten contamination elimination diet underwent urinary GIP determination at T0 and after challenge with 5 or 10 mg gluten. Urine GIP concentration was determined by an immunochromatographic assay. RESULTS: In study A, 51 of 150 baseline urine samples were GIP+ on GFD and 7 of 17 were GIP+ after the zero-gluten challenge, whereas only 55 of 81 were GIP+ after the 10–1, 000 mg gluten challenges. There was no significant change in the 24-hour urinary GIP when increasing gluten from 10 to 1, 000 mg. In study B, 24 of 24 baseline urine samples were GIP−, whereas 8 of 24 were GIP+ after 5 or 10 mg of gluten. DISCUSSION: Traces of gluten in the standard GFD may cause positivity of urinary GIP determination, whereas a false negativity is common after a gluten intake of 10–1, 000 mg. Owing to the impossibility of standardizing the test in normal conditions, it seems unlikely that urinary GIP determination may represent a reliable tool to assess the compliance to the GFD of patients with celiac disease or other gluten-related disorders.